Climate imprints during the 'Medieval Climate Anomaly' and the 'Little Ice Age' in marine records from the Alboran Sea basin - Nieto-Moreno, V.; Martínez Ruíz, Francisca C.; Giralt, Santiago; Gallego-Torres, D.; García-Orellana, Jordi; Masqué, Pere; Ortega-Huertas, M. (The Holocene, 2013)
An integrated multiproxy analysis from westernmost Mediterranean hemipelagic sediments has provided further insights into natural climate variability and forcing mechanisms in this region during the last two millennia. Two deep-sea marine records, with a robust age model provided by the activity-depth profiles of 210Pb and 137Cs, together with 14C dating, allowed us to perform a detailed reconstruction of paleoenvironmental and paleoceanographic responses during the 'Medieval Climate Anomaly' (MCA), the 'Little Ice Age' (LIA), the Industrial period (IP) and the second-half of the 20th century. Decreasing trends of fluvial-derived element (Si) and a increasing eolian input (Zr/Al ratio) characterized the MCA and the second-half of the 20th century as prevalent dry periods, while generally humid conditions are evidenced during the LIA and the IP, in accordance to a positive and a negative mode of the North Atlantic Oscillation (NAO), respectively (Trouet et al., 2009). The LIA developed as a sequence of successive short and abrupt dry-humid phase alternation. Furthermore, a noteworthy and sharp decrease of redox-sensitive elements (V/Cr and Ni/Co ratios) and coarser sortable silt at ad 1450 and 1950 yr, support more energetic hydrodynamic conditions at this time (oxygenated bottom waters and faster bottom currents), likely promoted by strengthened cooler waters flowing into the Mediterranean Sea. © The Author(s) 2013. We are grateful to CSD2006-00041 (TOPOIBERIA) and CSD2007-00067 (GRACCIE) projects. Peer Reviewed